Diversity of Sea Cucumbers (Holothuroidea) in the Waters of Sarang Island and the Nenek Strait, Batam City, Riau Islands, Indonesia - Devi Novianti; Ramses Ramses; Ismarti Ismarti; Fitrah Amelia (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: Sea cucumbers (Holothuroidea) are key benthic organisms that contribute to coastal ecosystem stability through bioturbation, organic matter decomposition, and their role in marine food webs. However, despite their ecological and economic importance, information on the diversity and community structure of sea cucumbers in the waters of Batam City, remains limited. This study aimed to analyze the diversity of sea cucumbers in the waters of Sarang Island and the Nenek Strait, as a basis for evaluating ecological conditions and supporting sustainable marine resource management. Methodology: Sampling was conducted in the intertidal zone using the sweeping method during nighttime to accommodate the nocturnal activity of sea cucumbers, using two transects at each sampling station. Species identification was based on morphological and visual characteristics, while environmental parameters such as temperature, pH, salinity, dissolved oxygen, water transparency, and current velocity were measured in situ. Findings: Five sea cucumber species were identified, namely Stichopus herrmanni, Holothuria leucospilota, H.scabra, Bohadschia aegyptia, and H. fuscopunctata. Community structure was then analyzed using the Shannon–Wiener diversity index (H’), evenness index (E), and Simpson’s dominance index (C). At Sarang Island, 25 individuals representing five species were recorded, with Actinopyga mauritiana dominating 64% of the population, resulting in moderate diversity (H’ = 0.576), low evenness (E = 0.358), and high dominance (C = 0.453). In the Nenek Strait, 22 individuals from three species were identified, showing moderate diversity (H’ = 1.059), high evenness (E = 0.964), and low dominance (C = 0.360), actinopyga mauritiana dominated 64% of the population, likely due to its higher tolerance to local environmental conditions and its preference for sandy–muddy substrates commonly found in the study area, indicating a more balanced community structure. Contributions: These findings highlight spatial variation in sea cucumber communities related to habitat characteristics and ecological pressure, contributing baseline scientific data on the diversity and community structure of Holothuroidea in Batam coastal waters